Preface: 10th International Symposium on Social Science (ISSS 2024) - Chen, Xincheng; Lee, Caroline (Transactions on Social Science, Education and Humanities Research, 2024)
The organizing Committee of the 10th ISSS warmly welcomes you to join the 10th International Symposium on Social Science (ISSS 2024), it was held on March 9-10, 2024 in Xi’an City, China. This conference was sponsored by Research Center of Engineering and Science, and was attended by researchers, entrepreneurs, government agencies and policy-makers, postgraduates. This 10th ISSS was held offline & online. The aim of ISSS is to provide a platform for educators, artists, scholars, managers, graduate students and sociologists from different cultural backgrounds to present and discuss research, developments and innovations in the fields of Social Science. We would like to thank the organizing committee, scientific committee and reviewers for their hard works in paper reviewing. We also would like to express our gratitude to the authors for contributing their research result to the conference. All full paper submissions to this 9th ISSS could be written in English only and were sent to at least two reviewers and evaluated based on originality, technical or research content or depth, correctness, relevance to conference, contributions, and readability. This 10th ISSS had received 116 manuscripts, and more than 40 submissions had been accepted by our reviewers. With our warmest regards, Xincheng Chen, Caroline Lee Conference Organizing Chairs Wuhan, China